Spray drying encapsulation of essential oils: Insights on various factors affecting the physicochemical properties of the microcapsules - Phanse, Shirish K.; Chandra, Sudeshna (Flavour and fragrance journal, 2024)
Spray drying is a process that involves instantaneous conversion of a liquid or slurry into a free‐flowing powder in the presence of hot air or nitrogen gas current in a drying chamber. The technique is usually used to encapsulate active molecules like essential oils, plant extracts, fragrances, flavours and enzymes within a wall material. The encapsulation provides chemical and physical stability to the actives by converting them into free‐flowing powders which prevents their susceptibility to external atmospheric conditions like temperature, humidity, UV exposure and chemical oxidation. Spray drying encapsulation has an edge over other encapsulation techniques because it is fast, simple, efficient and economically feasible. The article focuses on encapsulating various essential oils within natural polymers and emulsifiers by spray drying methods to form stable microcapsules. The review also provides information on different types of spray drying equipment and process parameters like the type of atomiszer and nozzles, inlet–outlet temperature and type of cyclones. All the process parameters and materials are found to influence the physicochemical properties of the microencapsulates of essential oils. The review also discusses the effects of process parameters and materials on the encapsulation efficiency, moisture content, bulk and tapped density, agglomeration properties and thermal stability of the microencapsulates. Thus, the consolidated review will provide an overview of various optimization parameters and governing factors for obtaining microencapsulates of essential oils. Encapsulation of essential oils and factors affecting the physicochemical properties of spray‐dried essential oil microcapsules.